Infinitely many solutions for a class of quasilinear equation with a combination of convex and concave terms - Teng, Kaimin; Agarwal, Ravi P. (Topological Methods in Nonlinear Analysis, 2017)
We consider the following quasilinear elliptic equation with convex and concave nonlinearities: \begin{equation*} -Δ_p u-(Δ_pu^2)u+V(x)|u|^{p-2}u=λ K(x) |u|^{q-2}u+μ g(x,u),\quad \text{in }\mathbb{R}^N, \end{equation*} where $2≤ p< N$, $1< q< p$, $λ,μ\in\mathbb{R}$, $V$ and $K$ are potential functions, and $g\in C(\mathbb{R}^N×\mathbb{R},\mathbb{R})$ is a continuous function. Under some suitable conditions on $V,K$ and $g$, the existence of infinitely many solutions is established.